Unlocking Islamic Consumer Behaviour on Gen Z: The Impact of E-Wallet Usage, Lifestyle, and Self Control - Indri Ayu Saputri; Muh Shadiqul Fajri AF; Angelita S. Villaruel (Al-Intaj)
Purpose: This study aims to examines the impact of e-wallet usage, lifestyle, and self-control on the Islamic islamic consumption behavior of Generation Z. By integrating these factors, it seeks to offer insights into consumer behavior from an Islamic perspective.